2015
DOI: 10.1165/rcmb.2014-0493oc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation along the Histamine Pathway in Children with Allergic versus Nonallergic Asthma

Abstract: Histamine is an important mediator in the pathogenesis of asthma. Variation in genes along the histamine production, response, and degradation pathway may be important in predicting response to antihistamines. We hypothesize that differences exist among single-nucleotide polymorphisms (SNPs) in genes of the histamine pathway between children with allergic versus nonallergic asthma. Children (7-18 yr of age; n = 202) with asthma were classified as allergic or nonallergic based on allergy skin testing. Genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Our current findings suggest that the variant may result in decreased expression/function of the enzyme leading to histamine accumulation and exaggerated response to histamine which we observed in our study. We previously found that HNMT -1639 was associated with the allergic asthma phenotype in African American children (Anvari et al, 2015). Therefore, this SNP may have significance in disease pathophysiology and severity particularly among specific racial groups.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our current findings suggest that the variant may result in decreased expression/function of the enzyme leading to histamine accumulation and exaggerated response to histamine which we observed in our study. We previously found that HNMT -1639 was associated with the allergic asthma phenotype in African American children (Anvari et al, 2015). Therefore, this SNP may have significance in disease pathophysiology and severity particularly among specific racial groups.…”
Section: Discussionmentioning
confidence: 96%
“…We also conducted a stratified analysis among the two major racial groups included in the study (African American and Caucasian) due to our previous findings that histamine genotype was most strongly associated with allergic asthma phenotype in African American children (Anvari et al, 2015). Furthermore, the contributions of histamine to disease are particularly important to understand among African American children due to increased asthma prevalence, morbidity, and mortality in this group when compared to other racial groups as well as an increased prevalence of the allergic asthma phenotype (Akinbami, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early investigation of Laser Doppler flowimetry have revealed minimal differences related to age and race [18]. Presumed race related differences may instead be related to observed genetic variation in the histamine production, response, and degradation pathway [19]. The advanced model provides a much more precise way to describe the variability of histamine response in population and suggests broader application of HILD method in allergy pharmacodynamic research.…”
Section: Discussionmentioning
confidence: 99%